The ontological foundations of McTaggart's argument on the unreality of time - Kovanlıkaya, Aliye. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1994., 1994)
In this thesis, it is attempted to investigate the ontological foundations of McTaggart's argument on the unreality of time which is generally considered independently from McTaggart's ontology. It is also aimed to show that McTaggart's ontology is essential for a proper understanding of the argument on the unreality of time. According to McTaggart, the Universe is the substance which conta~ns the contents of an infinite number of substances which are its parts. The Universe as a whole is a nonchanging substance. The Universe and its parts are all spiritual substances. Any change in anyone part of the Universe would mean the change of the Universe; that is to say the destruction of the Universe itself. What McTaggart means when he states that time is unreal is that existence as such cannot have temporal dimension. The thesis is aimed to show that McTaggart's claim that time is unreal is a consequence of his ontology in which there is no place for change and thus for existing events. It is also argued, in the thesis, that the critiques of McTaggart's argument from different points of views do not apply to the argument because they do not considered McTaggart's ontology which gives rise to the rejection ofthe reality of time.
Keywords: Philosophers -- England.; Time.